APOE4 Promotes Tonic-Clonic Seizures, an Effect Modified by Familial Alzheimer’s Disease Mutations - Lamoureux, Lorissa; Marottoli, Felecia M.; Tseng, Kuei Y.; Tai, Leon M. (Frontiers in Cell and Developmental Biology, 2021)
Seizures are emerging as a common symptom in Alzheimer’s disease (AD) patients, often attributed to high levels of amyloid β (Aβ). However, the extent that AD disease risk factors modulate seizure activity in aging and AD-relevant contexts is unclear. APOE4 is the greatest genetic risk factor for AD and has been linked to seizures independent of AD and Aβ. The goal of the present study was to evaluate the role of APOE genotype in modulating seizures in the absence and presence of high Aβ levels in vivo. To achieve this goal, we utilized EFAD mice, which express human APOE3 or APOE4 in the absence (EFAD-) or presence (EFAD+) of familial AD mutations that result in Aβ overproduction. When quantified during cage change day, we found that unlike APOE3, APOE4 is associated with tonic-clonic seizures. Interestingly, there were lower tonic-clonic seizures in E4FAD+ mice compared to E4FAD- mice. Restraint handing and auditory stimuli failed to recapitulate the tonic-clonic phenotype in EFAD mice that express APOE4. However, after chemical-induction with pentylenetetrazole, there was a higher incidence of tonic-clonic seizures with APOE4 compared to APOE3. Interestingly, the distribution of seizures to the tonic-clonic phenotype was higher with FAD mutations. These data support that APOE4 is associated with higher tonic-clonic seizures in vivo, and that FAD mutations impact tonic-clonic seizures in a paradigm dependent manner.